Placental outcomes of phthalate exposure - Warner, Genoa R. (Reprod Toxicol, 2021)
Proper placental development and function relies on hormone receptors and signaling pathways that make the placenta susceptible to disruption by endocrine disrupting chemicals, such as phthalates. Here, we review relevant research on the associations between phthalate exposures and dysfunctions of the development and function of the placenta, including morphology, physiology, and genetic and epigenetic effects. This review covers in vitro studies, in vivo studies in mammals, and studies in humans. We also discuss important gaps in the literature. Overall, the evidence indicates that toxicity to the placental and maternal-fetal interface is associated with exposure to phthalates. Further studies are needed to better elucidate the mechanisms through which phthalates act in the placenta as well as additional human studies that assess placental disruption through pregnancy with larger sample sizes.